I'm feeling lucky! Applying Google Maps and Google Street View in environmental criminological research - Vandeviver, Christophe (2013)
Online applications such as Google Maps (GM) and Google Street View (GSV) have become increasingly available. In addition to the many benefits such applications have in our daily lives and the concerns expressed by law enforcement agencies that such applications could result in changing offending patterns and habits, the availability of these applications opens up several new perspectives for environmental criminologists to conduct research. In this presentation, three potential uses of GM and GSV in environmental criminological research are demonstrated. Drawing on personal experiences and results from earlier research, it is explained how GM and GSV can be used to study (1) the target selection process of burglars and (2) the awareness space and journey to crime of burglars. Additionally, (3) it is discussed how GM and GSV could also be a useful and potentially time-saving tool to help chart the built environment in criminological research